From science as solution to science as suspect: science fiction and the canonical decline of technoidealism - Fuhrer, Nathan (My University, 2021)
Edified in Isaac Asimov's canonical Foundations trilogy, the exemplification of science as a panacea to human quandaries--herein referred to as technoidealism--is a central element of the 1950's science-fiction canon. Faced with a period of upheaval and a wave of new science fictions authors, this article explores the manner in which this assumption is modified, complicated, and popularly rejected. Drawing on the work of authors such as Isaac Asimov, Frank Herbert, Philip K. Dick, Jeff Somers, and Iain Reid, the technoidealist impulse serves to highlight the utopian current undergirding Asimov's work and the genre's complication of the human-science relationship. In drifting from its nascent futurist idealism, the literary endorsement of "science as solution" has veered toward "science as suspect" through a complication and reproval of the technoidealist assumption.
Keywords: science fiction; technoidealism